Study of lithium carbonate and ascorbate proliferative properties on transplantable Lewis lung carcinoma metastasis model - D. E. Frolova; I. Yu. Torshin; V. V. Rastashansky; M. V. Filimonova; O. A. Gromova (Фармакоэкономика)
Objective: to study the antitumor effects of organic lithium salt (lithium ascorbate) in different doses in comparison with inorganic lithium salt (carbonate).Material and methods. Two series of experiments were carried out on the effect of lithium preparations on the dynamics of transplantable Lewis lung carcinoma (LLC) growth and metastasis in F1 mice (CBA × C57Bl/6j). In the first series, a comparative study of the effects of different lithium ascorbate doses (1 and 10 mg/kg/day based on elemental lithium) was performed, and in the second series, a comparison was made of the effects of lithium ascorbate and carbonate when used at the same dose (5 mg/kg/day).Results. Significant antitumor effects were found for lithium ascorbate lower doses (1 and 5 mg/kg/day). A statistically significant antitumor effect of lithium ascorbate was observed from Day 10 throughout the entire observation period (tumor growth inhibition index (TGII) 30–40%). The antitumor effect of lithium carbonate in this experiment was less pronounced and stable (TGII 20–30%). No antimetastatic effect was observed with both preparations.Conclusion. Subchronic intragastric administration of lithium ascorbate and carbonate to tumor-bearing animals at a daily dose of 5 mg/kg, an antitumor effect is observed, manifested by LLC growth inhibition. Effective and safe antitumor doses of lithium ascorbate are in the range of 1–5 mg/kg.